(untitled) (Research, Society and Development, 2022)
Objective: To identify the adoption and acceptance of the use of technologies by the elderly public. methods: The Joanna Briggs Institute (JBI) methodology will be used to search indexed literature in languages ​​published in English, Spanish and Portuguese. They will be collected in 20 databases, and the reference lists of included studies will be manually searched. Two authors will independently evaluate titles, abstracts and full texts according to eligibility criteria. A customized data extraction form will be used to extract data from the included studies, which will be: (1) Studies in English, Portuguese and Spanish; (2) studies involve older adults (60 years and over) who use technologies; (3) empirical studies with quantitative, cross-sectional or longitudinal data, (4) letters to the editor and editorials, (5) published in all available years (1993 to 2022). Results: The results will be presented in a table format with a narrative summary.